2013
DOI: 10.1111/hdi.12024
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of providing maintenance hemodialysis in a resource poor country: Experience from a single teaching hospital in Lagos, Southwest Nigeria

Abstract: Providing maintenance hemodialysis is associated with high costs and poor outcomes. In Nigeria, more than 90% of the population lives below the poverty line, and patients with end-stage renal disease (ESRD) pay out-of-pocket for maintenance hemodialysis. To highlight the challenges of providing maintenance hemodialysis for patients with ESRD in Nigeria, we reviewed records of all patients who joined the maintenance hemodialysis program of our dialysis unit over a 21-month period. Information regarding frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
(37 reference statements)
3
11
0
Order By: Relevance
“…Chronic glomerulonephritis as seen in 44.6% was the commonest aetiology cause of CKD among our patients. This is similar to the report of Oluyombo et al, and Okaka et al [6,7], but in contrast to the indings of Bello et al, who reported hypertension as the cause of CKD in about half of their patient population [8]. Majority of our patients with chronic kidney disease presented very late with established complications.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Chronic glomerulonephritis as seen in 44.6% was the commonest aetiology cause of CKD among our patients. This is similar to the report of Oluyombo et al, and Okaka et al [6,7], but in contrast to the indings of Bello et al, who reported hypertension as the cause of CKD in about half of their patient population [8]. Majority of our patients with chronic kidney disease presented very late with established complications.…”
Section: Discussionsupporting
confidence: 92%
“…A high percentage (43.6%) of patients were lost to follow up during this period due to reasons which may not be unrelated to inancial constraints, traditional belief, and concept about the disease among others. A similar igure was reported by Meremo et al in Tanzania [16] and Bello et al in a Nigerian study [8]. Causes of death were inadequate dialysis due to inancial constraints with its attendant complications, poor compliance to medication including antihypertensive, and sepsis among others.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As the number of patients afflicted grows exponentially, the available resources become more and more limited. In addition, accurate and timely diagnosis, the cost of dialysis, the access to dialysis facilities and the number of trained nephrologists are all contributing factors [6,7]. For example, there are a few pediatric nephrologists in LMIC: 1/500,000 children in Egypt, 1/10 million in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…But its government spends only 0.9% of its GDP on health, well below the low and middle income country average of 3.0% and a fraction of the global mean of 6.8% [13]. Bello et al [13] previously reported that the majority of end-stage renal disease patients in Nigeria are dialysed less than once weekly and that the mean haemoglobin at the time of commencing haemodialysis is 73 g/L [14]. In addition to managing hypertension, diabetes and albuminuria with established treatments, Nigerian nephrologists need to make rationing decisions on CKD therapies that are routinely available in other LMIC countries.…”
mentioning
confidence: 99%